AB1180 Subclinical temporo-mandibular joint (TMJ) involvement in juvenile idiopathic arthritis (JIA) detect by screening imaging. (23rd January 2014) - Gattinara, M.; Del Giudice, E.; Failoni, S.; Mastaglio, C.; Donati, C.; Pontikaki, I.; Meroni, P.L.; Gerloni, V.
Abstract : Background: Juvenile Idiopathic Arthritis (JIA) has been shown to involve the temporo-mandibular joint (TMJ) and the facial growth with a high frequency. Arthritis in this joint is often not associated with pain and clinical signs are usually poor Objectives: To evaluate the validity of different TMJ screening methods we have studied 42 patients (32 female-10 male) mean age 15.1 yrs (range 6.8 -31.4), mean disease onset age 8.0 yrs (range 1-16) mean disease duration 6.6 yrs (range 0.1-21.4) Methods: Our population included 42 consecutive cases of JIA without TMJ clinical symptoms (28 pauci, 9 poly, 2 systemic and 3 ERA HLA B27+). 28/42 patients (66%) showed an active disease with high flogistic indexes while in 14/42 (33%) the arthritis was inactive.23 patients were studied only with ultrasound imaging (US) of the TMJ, 9 cases performed only a MRI of the TMJ, while 10 patients have done the exams both.Finally 12 healthy subjects (7 female - 5 male) with a mean age of 11.3 yrs (range 5.0-21.0) were included in the study. 7 subjects performed only an US while 1 was investigated only with MRI. In 4 cases US and MRI were done together. The parameters calculated in both investigation were a) axial and coronal capsular and synovial thickening, b) erosions, c) synovial effusion, d) disc morphology and e) condylar translation movement Results: Condylar translation was significantly reduced (p<0.05) in JIA pts (mean 7.60 range 0.1-12 SD 3.1) vs controls (mean 8.76 range 4-10.7 SD 2.2), axial capsular thickening was significantly increase (p<0.01) in JIA (mean 1.29 range 0.6-3.4 SD 0.5) vs control (mean 1.20 range 0.5-2.4 SD 0.5) and in the same way, coronal thickening was significantly (p<0.001) increased in JIA (mean 1.32 range 0.5-3.5 SD 0.5) vs control (mean 1.25 range 0.5-2.3 SD 0.4).Using MRI erosions were seen in 22/38 joints of 19 pts (58%)in the coronal section and in 18/38 joints (47%) in the axial section while normal condylar profile was seen only in 7/38 joints (18%) using both sections Conclusions: In conclusion US and MRI seems to be useful exams to investigate TMJ involvment in JIA showing an high rate of abnormality also in asymptomatic pts Disclosure of Interest: None Declared